Primary Headache Characters and Coping Strategies among Medical Students of King Saud University in Riyadh, Saudi Arabia - Alshibani, Mohammed G; Alalwan, Abdulaziz I; Alluhaymid, Yousef M; Mogheerah, Bayan A Al- (Archives of Clinical and Biomedical Research, 2023)
Objectives: To assess and determine the prevalence of primary headache characteristics and the coping strategies among Medical Students of King Saud University in Riyadh, Saudi Arabia. Medical students are exposed to more psychological and physical stressors than other students, affecting their quality of life, performance and academic achievement. Methods: The study was a cross-sectional observational study whereby electronic questionnaires were sent to 283 medical students at King Saud University in Riyadh, KSA, in their third, fourth and fifth years. The questionnaire collected demographic data and questions about the primary headache character and the coping mechanism/strategies used. Results: The results showed a prevalence rate of about 100% for one year. The most common diagnosis was migraine without aura (57.1%), followed by infrequent TTH (55.4%) for both genders. No student reported chronic TTH. 78.6% reported no impact of the headache on their academic performance. However, for those who reported negative impact, the greatest proportion was among the students with migraine with aura (33.3%) and frequent TTH (20%). Self-medication was the most common, with most students using Simple analgesics such as Paracetamol (58.7%- 65.6%) followed by Triptan (e.g., Sumatriptan) ((14.4%-17.5) for relief. Conclusion: The prevalence of headaches among the medical students at King Saud University in Riyadh, Saudi Arabia, was about 100% which is higher than the prevalence average among the general population. However, the headache did not significantly impact their academic performance. The study recommends longitudinal studies to understand why the prevalence rate is high and recommend interventions.